Characterization of amorphous silica and crystalline silica from rice husk ash on water filtration application - Zainal, Nur Saadah (2020)
The presence of water pollution which consists of heavy metals, fecal and others has produced a major problem. These can lead the water to the toxicity and the impurity of water will be disrupted. Therefore, it would not be safe to drinks and could be threatening to live health. In addition, the current market now is dealing with high-cost production to develop ceramic membranes and has been using expensive material to make the filtration system works. In order to challenge the issue, the preparation of ceramic water filtration at low-cost production and using an effectively silica from natural waste rice husk was evaluated. Rice husk was fired at 700ºC and 1000ºC respectively and produced rice husk ash which mutated to amorphous and crystalline silica. Five samples were fabricated after been mixed with the compositions of rice husk ash, kaolin clay, and wheat flour, used at 40:40:20 ratios by weight respectively. The fabrications of the ceramic membrane were conducted by using dry pressing. The samples then were dried in the oven at 60ᵒC for 1 hour followed by sintering at 1000ᵒC respectively. These samples (OO, C1, C2, N1, and N2) were tagged based on unwashed and washed material with the chemical. The properties of silica which are the microstructure and pore size, from rice husk ash were obtained by using Scanning Electron Microscopy (SEM), X-Ray Fluorescence (XRF) and x-ray diffractometer (XRD). Effect of silica content in ceramic filtration membrane was investigated and characterized in term of porosity, density, water absorption, membrane hardness, pore size, flow rate, the turbidity of water (before and after filtration) and pH value. From the result, sample C2 was the best option to support the objective by 98.60% silica content, 64.82% of porosity, 1.1433 mg/cm3 of density, 40.59% of water absorption, 171.0 Hv of hardness, 0.177 l/hr of flowrate and pH of 7.62 of water after filtration. In general, the quality of the ceramic filter membrane is reliant on the raw material, while the flow rate and water clarity are dependent on the pore size of the filter membrane.